Impact of Quality of Work Life on Employees’ Commitment to Private Commercial Banks of Hetauda - K.C., Gautam; Silwal, Yam Bahadur; K.C., Sudarshan; Paudel, Saroj; Singh, Madhu Kumar; Neupane, Sushil (Nepal Journal of Multidisciplinary Research, 2023)
The quality of work life (QWL) and employee commitment have been a subject of interest among managers and academicians for a long period to enhance organizational performance. Quality of work life is the quality of the relationship between employees and the total work environment, concern for the impact of work on individuals as well as on organisation effectiveness, and the idea of participation in organisational problem-solving and decision-making in concurrence with the ascertained importance of an employee’s role in the service exchange process. This present study attempts to test the relationship between the quality of work life and employee commitment in the commercial bank of Hetauda. The research is a cross-sectional field survey and correlational study. Among a total of 240 employees currently working in Hetauda, 150 employees were selected as the sample of the study in 2023. In order to fulfil the research objectives, the primary data were collected using structured questionnaires. Purposive sampling was used to collect data. Data were analyzed using both descriptive and inferential statistics tools as per the requirement to study the responses and findings were derived. The result of the study indicated that there was a positive correlation between the quality of work life (supervisor support, working conditions, professional development, adequate remuneration and work-life balance) and employee commitment (affective commitment, normative commitment and continuance commitment). The study concluded that there were theoretical and practical implications. Regression analysis showed that there was a significant impact of quality work life on employees (affective commitment, normative commitment and continuance commitments).